FIRE RISK ASSESSMENT OF THE SEPARATION UNITS IN SELECTED OIL AND GAS COMPANIES IN RIVERS STATE - Ogbowu, E. N.; Ugwoha, E.; Amah, V. (International Journal of Innovations in Engineering Research and Technology, 2025)
This study focused on fire risk assessment of the separation units in selected oil and gas companies in Rivers State. Analytical and descriptive research designs were adopted. Separation unit which is among the most fire vulnerable units was considered in this study. Twelve fire-related hazards associated with the separation units were ascertain using Fire and Explosion Risk Assessment (FERA) (2020) guideline and the hazards were grouped into flammable sources and heat/ignition sources. The risk assessment was conducted by ranking of the hazards based on their risk score using Conventional Risk assessment (CRA) and Weighed Risk Assessment (WRA). The risk score of the fire-related hazards were evaluated using their severity and likelihood. The severity and likelihood of the hazards were determine using questionnaire administered to four hundred field-workers in three selected oil and gas firms in the study area and a predetermined factor (response weight) was assigned to field-workers based on their safety-related experience. The results revealed that fire-risk hazards in the separator unit were mostly classified under “High risk and Extreme risk” using Risk Assessment Matrix because their risk scores were greater than the 12.00 threshold for low risk hazard. The fault tree analysis (FTA) revealed that “Leakage of Hydrocarbon due to failure from high pressure flow” and “Failure of temperature controller” are unique fire-risk hazards with most devastating fire effect that must not be allowed to co-exist in the separation units. It was concluded that separation units of the oil and gas companies are high-to-extreme risk to fire accidents. It was therefore recommended that management of the oil and gas companies should pay a closer attention to the fire-safety of the separation units because it is one of most vulnerable unit to fire incident in the oil and gas companies